A Multivariate and Phylogenetic Analysis of Blackfoot Biographic Art: Another Look at the Deadmond Robe. (3rd July 2017) - Lycett, Stephen J.
Abstract : The Deadmond robe, an example of painted biographic art attributed to Blackfoot, is thought to date from the last two decades of the nineteenth century. A previous frequency seriation analysis reported in this journal provided results indicative of such a date. Here, this claim is reassessed. Two multivariate statistical methods were utilized that circumvent certain methodological difficulties encountered during the earlier comparative frequency seriation. A further aim of the analyses was to provide a test case for the application of evolutionary-phylogenetic methods to these kinds of data. The two multivariate analyses provide results that entirely corroborate the date of the Deadmond robe. The phylogenetic analyses meanwhile indicate that such methods can be applied in comparable ethnographic and archaeological circumstances where less contextual information may be known. The analyses reiterate that the Deadmond robe forms an important element in the historical legacy of biographic art from the Northwestern Plains.